VI Winter School of molecular, quantum acoustics and hydroacoustics and ultrasounds - DOBRZAŃSKI, M. M. (Archives of Acoustics, 1977)
VI Winter School of Molecular, Quantum Acoustics and Hydroacoustics and Ultra-sounds was hold between 8-14 March at Szczyrk. The promotor of the Winter School was the Institute of Physics of Silesian University in Gliwice and the newly organized Section of Molecular and Quantum Acoustics attached to the Upper Silesian Department of the Polish Society of Acoustics (PTA). The Chairman of Organizing Committee was dr StanislawSZYMA.The School was attended by over 30 participants from 10 scientific centres. In course of the School six sessions were held at which 27 lectures and reports were delivered giving a general review of the research work in Poland in quantum acoustics, acoustoelectronics, ultrasonic spectroscopy, hydroacoustics and ultrasounds.